PENGARUH CURAH HUJAN TERHADAP FLUKTUASI PRODUKSI PENANGKAPAN IKAN DI LAUT (PERAIRAN CILACAP) - Lusiani; Andi Hendrawan; Wahikun (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
The objective to be achieved in this paper is to analyze whether or not the effect of rainfall on fluctuation of fish production at sea in Cilacap waters. The method in this study is a combination of survey and literature review. In this study the authors take the location in the waters of Cilacap. The data used are secondary data obtained from the Central Bureau of Statistics of Cilacap Regency. The data sample used is statistical data in the period of 4 years, starting from 2013 until 2016. The results show that rainfall is not comparable with the production of captured marine fishery. This occurs over four periods, from 2013 to 2016. The production of marine capture fisheries is not significantly affected by rainfall, possibly influenced by some of the more significant factors related to weather and climate in the area. The conclusion of this research is that rainfall does not significantly influence fluctuation of sea fish production.